Cardiovascular Patient's Anxiety in the Time of the Covid-19 Pandemic - Pole, Jasper Suinite; Andri, Juli; Padila, Padila (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the level of anxiety of patients with cardiovascular disorders during the COVID-19 pandemic. The type of research used in this research is quantitative research with a cross-sectional approach. The results showed that the level of anxiety of respondents who were included in the standard/not anxious category was four respondents (5.4%), mild anxiety was 27 respondents (36.5%), moderate anxiety was 33 respondents (44.6%), and anxious weight as many as ten respondents (13.5%). In conclusion, the anxiety level of patients with cardiovascular disorders during the COVID-19 pandemic was in the moderate anxiety category. Keywords: Anxiety, Cardiovascular, COVID-19